Pro Windows 8.1 Development with XAML and C# - Liberty, Jesse (Apress, 2014)
Windows 8.1 apps are revolutionizing development on the Windows platform. Fast, fluid, tactile and chrome-free, they provide a brand-new look and feel for Windows users. These apps rely on Microsoft's Windows 8 modern UI to provide their rich and engaging user experiences for both desktop and tablet users. The new UI in turn relies upon the Windows Runtime (WinRT) to give its apps unparalleled flexibility and power. Understanding this stack of new technologies and how they tie in to the proven C# language and the XAML standard is the subject of this book. Experienced writers Jesse Liberty, Phil Japikse, and Jon Galloway explain how you can get the most from Windows 8.1 by focusing on the features that you need for your project and bringing your existing C# coding knowledge to bear. They begin with a nuts-and-bolts examination of how the technologies fit together and show you everything you need to get up and running with the new platform. Once you have a good understanding on the basics, you progress to more advanced topics steadily increasing your understanding as a whole. This holistic knowledge is essential to truly master Windows 8.1 development. Each topic is covered clearly and concisely and is packed with the details you need to code effectively. The most important features are given a no-nonsense, in-depth treatment and chapters contain examples that demonstrate both the power and the subtlety of Windows 8.1.